Pengaruh Penghindaran Pajak terhadap Biaya Utang dengan Risiko Pajak sebagaiVariabel Moderasi - Dewi Kusuma Wardani; Nasya Anindhia (urn:nbn:id:umrah-jafi.v9i1.2025.001jiafi.v9i2, 2025)
The purpose of this study is to examine the effect of tax avoidance on the cost of debt, with tax risk as a moderating variable. Tax avoidance has the potential to create cash flow uncertainty and increase risk for creditors, and therefore, theoretically, it can influence the determination of a company's cost of debt. However, empirical findings regarding this relationship are still mixed. Secondary data was obtained from the annual reports of food and beverage manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2024. The sample was selected by purposive sampling with 136 observations analyzed with Moderated Regression Analysis (MRA), using SPSS version 24 software with multiple linear regression analysis techniques. The results indicate that tax avoidance does not affect the cost of debt. Tax risk is also unable to moderate the relationship between tax avoidance and the cost of debt. As for the control variables, leverage, profitability, and capital intensity were found to have a significant effect on the cost of debt. These findings indicate that creditors place more emphasis on a company's financial condition when determining the cost of debt than on tax avoidance practices and the level of tax risk.